Characteristics and evaluation of coastal erosion vulnerability of typical coast on Hainan Island - Fu, GuoWei; Cao, Chao; Fu, KaiZhe; Song, YanWei; Yuan, Kun; Wan, XiaoMing; Zhu, ZiAng; Wang, ZhaoFan; Huang, ZanHui (Frontiers in Marine Science, 2022)
Coral reefs are important coastal ecological barriers, but the rapid degradation of coral reefs under the influence of human activities and global climate change has increased the risk of coastal erosion. Based on the natural and social characteristics of the east coast of Qiongdong and the coastal erosion vulnerability index (CVI) method, this study selected 8 assessment indicators, such as shoreline change rate (U1). The Philippine method and the entropy weight method were used to calculate the comprehensive index weight, and the temporal and spatial distribution characteristics of the coastal erosion vulnerability of coral reefs on eastern Hainan Island were quantitatively evaluated by combining the CVI method and geographic information system (GIS) technology. The study area was divided into 5 grades: very low (31%), low (10%), moderate (28%), high (24%) and high vulnerability (7%), and the overall performance was moderate erosion vulnerability. The research showed that the interannual downward rate erosion of beach (U3) and the rate of change of the isobath (U2) of the beach were the main controlling factors affecting the vulnerability of coastal erosion in the study area, and the coastal dynamic factor had a greater impact than the other two factors. As a natural barrier, the coral reefs in the study area had good wave absorption and energy reduction, and the coral reef coasts showed low coastal erosion vulnerability. The verification results of the ROC-AUC method showed that the accuracy of erosion vulnerability was 68.9%, which provided an important reference for the ecological restoration of tropical coral reef biological coasts and the development and management of the Hainan Qiongdong coastal zone.